Long-term swimming training modifies acute immune cell response to a high-intensity session - Morgado, J. P.; Monteiro, C. P.; Matias, C. N.; Reis, J. F.; Teles, J.; Laires, M. J.; Alves, F. (European Journal of Applied Physiology, 2018)
Purpose: Long-term training influence on athletes` immune cell response to acute exercise has been poorly studied, despite the complexity of both chronic and acute adaptations induced by training. The purpose of the study is to study the influence of a 4-month swimming training cycle on the immune cell response to a high-intensity training session, during 24 h of recovery, considering sex, maturity, and age group. Methods: Forty-three swimmers (16 females, 14.4 ± 1.1 years; 27 males, 16.2 ± 2.0) performed a standardized high-intensity session, after the main competition of the first (M1), and second (M2) macrocycles. Blood samples were collected before (Pre), immediately after (Post), 2 h after (Post2h) and 24 h after (Post24h) exercise. Haemogram and lymphocytes subsets were assessed by an automatic cell counter and by flow cytometry, respectively. Subjects were grouped according to sex, competitive age groups, or pubertal Tanner stages. Results express the percentage of relative differences from Pre to Post, Post2h and Post24h. Upper respiratory symptoms (URS) and training load were quantified. Results: At M2, we observed smaller increases of leukocytes (M1: 14.0 ± 36.3/M2: 2.33 ± 23.0%) and neutrophils (M1: 57.1 ± 71.6/M2: 38.9 ± 49.9%) at Post; and less efficient recoveries of total lymphocytes (M1: - 22.0 ± 20.1/M2: - 30.0 ± 18.6%) and CD19+ (M1: 4.09 ± 31.1/M2: - 19.1 ± 24.4%) at Post2h. At Post2h, the increment of CD4+/CD8+ was smaller in youth (M1: 21.5 ± 16.0/M2: 9.23 ± 21.4%), and bigger in seniors (M1: 3.68 ± 9.21/M2: 23.2 ± 15.0%); and at Post24h late pubertal swimmers` CD16+56+ recovered less efficiently (M1: - 0.66 ± 34.6/M2: - 20.5 ± 34.2%). Conclusions: The training cycle induced an attenuated immune change immediately after exercise and a less efficient recovery of total lymphocytes, involving an accentuated CD19+ decrease. The concomitant higher URS frequency suggests a potential immune depression and a longer interval of susceptibility to infection.